2023
DOI: 10.3389/fmed.2023.1248465
|View full text |Cite
|
Sign up to set email alerts
|

Development of functional gastrointestinal disorder symptoms following laparoscopic cholecystectomy: a prospective cohort study

Ji Young Chang,
Hye-Kyung Jung,
Chang Mo Moon
et al.

Abstract: BackgroundThe casual relationship between the role of cholecystectomy and functional gastrointestinal disorders (FGIDs) are a controversial clinical challenge. This study aimed to investigate: (1) the overlap of FGIDs before cholecystectomy and its long-term outcome after surgery in patients with symptomatic cholelithiasis, and (2) the incidence of new-onset FGIDs after cholecystectomy.MethodsPatients with symptomatic gallstone disease who underwent elective, laparoscopic cholecystectomy were prospectively enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Further analysis of the data showed that 2 out of 40 patients in the EGPS group complained of an increase in the frequency of stool after surgery, while 8 of the patients in the LC group complained of an increase in the frequency of stool compared with before surgery, diarrhea or diarrhea worse than before surgery, ranging from 1 wk to 6 months after surgery. The study by Chang et al [ 12 ] showed that at one year of follow-up after cholecystectomy, a large number of patients developed symptoms of persistent functional gastrointestinal disease, including diarrhea, which is similar to our study. The causes of diarrhea after cholecystectomy may be related to changes in bile acid metabolism[ 13 ], changes in the intestinal immune environment[ 14 ], dysbiosis[ 6 ], etc .…”
Section: Discussionsupporting
confidence: 91%
“…Further analysis of the data showed that 2 out of 40 patients in the EGPS group complained of an increase in the frequency of stool after surgery, while 8 of the patients in the LC group complained of an increase in the frequency of stool compared with before surgery, diarrhea or diarrhea worse than before surgery, ranging from 1 wk to 6 months after surgery. The study by Chang et al [ 12 ] showed that at one year of follow-up after cholecystectomy, a large number of patients developed symptoms of persistent functional gastrointestinal disease, including diarrhea, which is similar to our study. The causes of diarrhea after cholecystectomy may be related to changes in bile acid metabolism[ 13 ], changes in the intestinal immune environment[ 14 ], dysbiosis[ 6 ], etc .…”
Section: Discussionsupporting
confidence: 91%